2021
DOI: 10.1002/jcp.30442
|View full text |Cite
|
Sign up to set email alerts
|

DL‐3‐n‐butylphthalide‐induced neuroprotection in rat models of asphyxia‐induced cardiac arrest followed by cardiopulmonary resuscitation

Abstract: Most patients that resuscitate successfully from cardiac arrest (CA) suffer from poor neurological prognosis. DL-3-n-butylphthalide (NBP) is known to have neuroprotective effects via multiple mechanisms. This study aimed to investigate whether NBP can decrease neurological impairment after CA. We studied the protective role of NBP in the hippocampus of a rat model of cardiac arrest induced by asphyxia. Thirty-nine rats were divided randomly into sham, control, and NBP groups. Rats in control and NBP groups und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, Pei et al and Hurt et al found TRPV1 by western blotting and by immunostaining in primary mouse and rat cardiomyocytes 6 , 34 . Furthermore, TRPV1 localization was demonstrated in murine embryonic stem cells (ESC) and in ESC-derived cardiomyocytes 35 , 36 . While the expression of TRPV1 mRNA in iPSC and unspecified human iPSC-derived cardiac cells was shown recently 37 , to our knowledge our study is the first to describe the expression and localization of the channel protein in hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pei et al and Hurt et al found TRPV1 by western blotting and by immunostaining in primary mouse and rat cardiomyocytes 6 , 34 . Furthermore, TRPV1 localization was demonstrated in murine embryonic stem cells (ESC) and in ESC-derived cardiomyocytes 35 , 36 . While the expression of TRPV1 mRNA in iPSC and unspecified human iPSC-derived cardiac cells was shown recently 37 , to our knowledge our study is the first to describe the expression and localization of the channel protein in hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…DL-3-n-butylphthalide (NBP) is a neuroprotective agent, originally isolated from celery seeds and has been shown to possess therapeutic efficacy in ischemic brain by suppressing neuroinflammation and maintaining the BBB. In rat models of 6-minute asphyxia-induced CA, IV NBP (10 mg/kg) infusion 10 minutes after resuscitation and delivered twice a day for 3 consecutive days improved neurological function up to 72 hours after CA [ 98 ]. NBP treatment reduced neuronal damage alongside ultrastructural mitochondrial damage, reduced apoptosis through the Jun N-terminal kinases and p38 mitogen-activated protein kinases (JNK/p38) pathway, and suppressed inflammatory response through the nuclear factor kappa light chain enhancer of activated B cells (NF-κB pathway).…”
Section: Neuroprotective Approaches In Ca-induced Brain Injurymentioning
confidence: 99%
“…In one ACA study in pigs, the initial rhythm converted from PEA to VF in 57% of pigs before CPR was begun ( Varvarousi et al, 2015 ). If a shockable rhythm occurs, 2–4 joules (J) could be applied for defibrillation, with 2 J most commonly used in recent rat models ( Hu et al, 2019 ; Yang et al, 2021 ). Electrical defibrillation can also have side effects, with too high defibrillation energy causing heart damage ( Ishigaki et al, 2016 ).…”
Section: Factors To Consider In Establishing An Aca Rat Modelmentioning
confidence: 99%